Comparing performance of Chromameter®, Mexameter® and full‐field laser perfusion imaging for measurement of ultraviolet B light‐induced erythema. (1st June 2015) - Qian, C. Y.; Yuan, C.; Tan, Y. M.; Liu, X. P.; Dong, Y. Q.; Yang, L. J.; Wu, P. L.; Wang, X. M.
Summary: Erythema induced by ultraviolet (UV)B light is a common skin reaction. Currently, three techniques, the Chromameter ® CR‐400, the Mexameter ® MX16 and full‐field laser perfusion imaging (FLPI), are widely used for dermatological evaluation of UVB‐induced erythema. However, there is little known about the comparative performance of these three techniques. This study was therefore designed to evaluate the effectiveness of the three techniques. Our findings showed that the performance of Chromameter and Mexameter for measurement of UVB‐induced erythema was very similar, while FLPI indicated acute erythema at D1 with the greatest fold change. Further studies of UVB dose‐dependence need to be carried out.